2010
DOI: 10.1063/1.3340799
|View full text |Cite
|
Sign up to set email alerts
|

The quantum N-body problem and the auxiliary field method

Abstract: Approximate analytical energy formulas for N-body semirelativistic Hamiltonians with one-and two-body interactions are obtained within the framework of the auxiliary field method. This method has already been proven to be a powerful technique in the case of two-body problems. A general procedure is given and applied to various Hamiltonians of interest, in atomic and hadronic physics in particular. A test of formulas is performed for baryons described as a three-quark system.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
113
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(115 citation statements)
references
References 41 publications
(11 reference statements)
2
113
0
Order By: Relevance
“…The method can also be extended to semirelativistic Hamiltonians [8] and to N -body systems [9]. In this last case, it is specially powerful for identical particles.…”
Section: The Auxiliary Field Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…The method can also be extended to semirelativistic Hamiltonians [8] and to N -body systems [9]. In this last case, it is specially powerful for identical particles.…”
Section: The Auxiliary Field Methodsmentioning
confidence: 98%
“…Formula (12) looks like a semiclassical approximation but this absolutely not the case. The AFM yields approximate N -body wavefunctions [9], and the relation (13) between p 0 and r 0 is a full quantum link, function of the quantum numbers of the system. At last, the value of r 0 (and thus of p 0 ) is the solution of a transcendental equation (14) which is the translation into the AFM variables of the generalized virial theorem [13].…”
Section: The Auxiliary Field Methodsmentioning
confidence: 99%
“…where ∑ M i=1 p p p i = 0 0 0 and R R R is the center of mass coordinate [16]. U(x) is a one-body potential and V (x) is a two-body potential.…”
Section: The Auxiliary Field Methodsmentioning
confidence: 99%
“…It can then be shown that the AFM solution of the Hamiltonian (2.1) is obtained by solving the following set of equations [16,17,18,19] …”
Section: The Auxiliary Field Methodsmentioning
confidence: 99%
See 1 more Smart Citation